OPTIMALISASI E-COMMERCE MELALUI TEKNOLOGI WEB MODERN (NEXT.JS, LARAVEL, DSB) SYSTEMATIC LITERATURE REVIEW - Denis Pratama; Andi Umi Kalsum; Radika Fibrilya Herman; Anisa Fitri; Kharisma Dewi; Dhimas Tribuana (Jurnal Teknologi dan Bisnis Cerdas, 2025)
The development of modern web technologies has become one of the strategic factors in improving the performance and competitiveness of e-commerce platforms in the digital era. This study employs a Systematic Literature Review (SLR) approach based on the PRISMA 2020 guidelines. A total of 20 articles published between 2020 and 2025 were identified as eligible for analysis. This review aims to identify development patterns, key contributions, research gaps, and future research directions related to the optimization of e-commerce using modern web technologies such as Next.js, Laravel, React.js, and Node.js. The synthesis results reveal five major clusters: (1) Performance Optimization & SEO Enhancement, (2) Scalability & System Architecture, (3) User Experience & Interface Design, (4) Security & Data Protection, and (5) Integration & Digital Empowerment for SMEs. The findings emphasize that the success of e-commerce optimization is not solely dependent on the adoption of modern frameworks, but also on the synergistic integration of system architecture, business strategies, and user experience.